2023
DOI: 10.1111/jen.13191
|View full text |Cite
|
Sign up to set email alerts
|

Glycerin‐based dispensers of fir oil reduce response of Asian citrus psyllid, Diaphorina citri, to citrus odours

Angela Chuang,
Lukasz L. Stelinski,
Lourdes Pérez Cordero
et al.

Abstract: The Asian citrus psyllid, Diaphorina citri Kuwayama, transmits the bacterial pathogen associated with huanglongbing, a fatal citrus disease. Alternatives to insecticides for D. citri management are being explored, given the development of insecticide resistance and the lack of efficient biological controls. Essential oils as pest repellents have shown some efficacy in laboratory and field evaluations; however, lack of an effective dispenser for field deployment has prevented their application. In this investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…A similar approach investigating the use of fir oil as repellent against D. citri was investigated recently. In this study, the authors assessed a reduction in the number of insects collected in areas treated with glycerin dispensers containing fir oil (Chuang et al, 2023). Research on H. halys by Zhang et al, 2014 found that plant essential oil blends (clove, lemongrass, and spearmint oil), as well as individual plant volatiles from those essential oils (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach investigating the use of fir oil as repellent against D. citri was investigated recently. In this study, the authors assessed a reduction in the number of insects collected in areas treated with glycerin dispensers containing fir oil (Chuang et al, 2023). Research on H. halys by Zhang et al, 2014 found that plant essential oil blends (clove, lemongrass, and spearmint oil), as well as individual plant volatiles from those essential oils (e.g.…”
Section: Discussionmentioning
confidence: 99%